Understanding the gendered coaching workforce in Spanish sport - Hinojosa-Alcalde, I.; Andrés, A.; Serra, P.; Vilanova, A.; Soler, S.; Norman, L. (International Journal of Sports Science & Coaching, 2018)
The present study focuses on the demographic and labor characteristics of coaches in Spain. Kanter`s theory on occupational sex segregation will be used as a guiding framework. The study was conducted with 1685 coaches (82.3% men and 17.7% women) from different sports and performance domains. The results show that there is an underrepresentation of women as coaches in Spain and data highlight that coaches` gender is related to three structural factors: opportunity, power, and proportion. The present data reveal that women are younger, less likely to be in a marriage-like relationship, less likely to have children, and more likely to have competed at a high level as an athlete when compared to their male counterparts. However, fewer women than men access and participate in coach education in Catalonia and the working status of women was different to that of men. To expand, women worked less hours, were more likely to be assistant coaches, and had less years of coaching experience. Understanding of how gender influences women`s access, progression, and retention in coaching in Spain illustrates the need for gender sport policies and practices in sport organizations. This approach can benefit not only women, but the diversity and enrichment of the coaching system